2009
DOI: 10.1016/j.physc.2009.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Towards beyond 1 GHz NMR: Mechanism of the long-term drift of screening current-induced magnetic field in a Bi-2223 coil

Abstract: The screening current-induced magnetic field in the (Bi,Pb) 2 Sr 2 Ca 2 Cu 3 O x (Bi-2223) insert coil proposed for a beyond 1GHz nuclear magnetic resonance (NMR) spectrometer may generate a long term field drift, resulting in a loss of field-frequency lock operation and an inability to make high resolution NMR measurements. The measured screening current-induced magnetic field of a Bi-2223 double-pancake coil exhibits a hysteresis effect at 4.2K that is reproduced by a numerical simulation based on a finite t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
59
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 30 publications
8
59
0
Order By: Relevance
“…We also reported that the temporal magnetic field drift due to screening current for a Bi-2223 coil is effectively suppressed by a current sweep reversal technique [6][7]. A similar effect was demonstrated for a 500 MHz (11.75 T) HTS/LTS NMR using a Bi-2223 innermost coil [8].…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…We also reported that the temporal magnetic field drift due to screening current for a Bi-2223 coil is effectively suppressed by a current sweep reversal technique [6][7]. A similar effect was demonstrated for a 500 MHz (11.75 T) HTS/LTS NMR using a Bi-2223 innermost coil [8].…”
Section: Introductionsupporting
confidence: 57%
“…The reduction rate depends on the coil shape and is mostly remarkable in the case of a minimum volume design [4]. The second problem is a temporal positive drift in the central magnetic field; the screening current relaxes with time due to flux creep, resulting in long term drift in the central magnetic field [4][5][6]. These effects are undesirable for NMR magnets as NMR requires a homogenous and stable magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…1 (black-solid line) shows the initial change in the magnetic field intensity with time measured by an NMR meter (Model PT 2025, Metrolab Instruments); note that the vertical axis is normalized to the NMR operation field. After attaining the operation current at t = 0 h, the magnetic field intensity increased with time at a rate of 1.9 Â 10 À5 (19 ppm)/h at first, and then tended to saturate at 5 Â 10 À8 /h (50 ppb/h) at t = 110 h. Screening current was induced in the Bi-2223 tape by the radial component of the NMR magnetic field, generating a negative central magnetic field at the coil center [15]. Relaxation of the screening current resulted in positive drift of the magnetic field intensity as seen in Fig.…”
Section: Initial Change In the Magnetic Field After Charging The Nmr mentioning
confidence: 99%
“…Its relaxation results in the positive drift of the central magnetic field with time, after the magnet is charged to the operation current [15]. If the temporal change in the screening current-induced magnetic field exceeds 3 Â 10 À6 (±1.5 ppm), the field-frequency lock system loses operation and it is impossible to achieve a high resolution NMR spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Slim ($1-mm radial build), it can be placed inside the magnet assembly, avoiding the disadvantages inherent in the conventional NbTi shim. We believe that the HTS shim described here will become a key design option for NMR magnets, including those operated LHe-free, even at > 4:2 K. Although not restricted to GHz-class NMR magnets, 1,[15][16][17] the HTS shim may find its dddddssdsdsd application in these NMR magnets, because each >1-GHz NMR magnet contains an insert of nested HTS coils, which may collectively be modeled as a thick-walled diamagnet.…”
mentioning
confidence: 99%